2017
DOI: 10.1016/j.cognition.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of language and visual perception in working memory

Abstract: How do perception and language interact to form the representations that guide our thoughts and actions over the short-term? Here, we provide a first examination of this question by investigating the role of verbal labels in a continuous visual working memory (WM) task. Across four experiments, participants retained in memory the continuous color of a set of dots which were presented sequentially (Experiments 1-3) or simultaneously (Experiment 4). At test, they reproduced the colors of all dots using a color w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
114
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(126 citation statements)
references
References 82 publications
12
114
0
Order By: Relevance
“…Second, visual memory for difficult-to-label information may be limited because it affords less opportunity to activate long-term memory representations. Souza and Skóra (2017) found that labeling colors (overtly or sub-vocally) improved younger-adult memory performance by activating long-term memory representations, rather than simply by adding verbal memory traces. If older adults' memory for easy-to-label colors was also comparatively 'boosted' because such colors automatically activated lexical, semantic representations that helped compensate visual memory, this would explain why this special benefit for easy-to-label colors in older adults was not completely abolished under suppression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, visual memory for difficult-to-label information may be limited because it affords less opportunity to activate long-term memory representations. Souza and Skóra (2017) found that labeling colors (overtly or sub-vocally) improved younger-adult memory performance by activating long-term memory representations, rather than simply by adding verbal memory traces. If older adults' memory for easy-to-label colors was also comparatively 'boosted' because such colors automatically activated lexical, semantic representations that helped compensate visual memory, this would explain why this special benefit for easy-to-label colors in older adults was not completely abolished under suppression.…”
Section: Discussionmentioning
confidence: 95%
“…Such translation of visual representations into verbal code has been found to improve visual memory performance in younger adults (Brown, Forbes, & McConnell, 2006;Souza & Skóra, 2017). Despite this, tasks are often assumed to measure either visual or verbal WM, perhaps incorrectly (e.g., Logie, 2018).…”
Section: Take Down Policymentioning
confidence: 99%
“…Thus, we do not argue that visual WM cannot be measured with long memory array intervals. For example, a recent study ( Souza and Skóra, 2017 ) have demonstrated that when given enough time (by using serial presentation) verbal encoding of colors can increase both the quality and quantity of the stored information.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of a recoding a visually presented stimulus depends on whether semantic associations are automatically accessed without labeling 5,33 . In Experiment 1 automatic semantic associations occurred; thus, the addition of rehearsing with a generated label offered no more benefit than accessing those stored associations 12,14,26 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies support that blocking rehearsal with articulatory suppression, repeating a word such as "the" over and over again, decreases performance compared with when someone rehearses 2,3 . Visual stimuli may also benefit from rehearsal when the stimulus is recoded into a verbal representation [4][5][6] . However, the benefit of labeling and rehearsal may depend on the working memory task [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%